2016
DOI: 10.1016/j.bej.2016.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Biofiltration of H 2 S in air—Experimental comparisons of original packing materials and modeling

Abstract: a b s t r a c tThe treatment of hydrogen sulfide using a biofilter packed with expanded schist and topped with a layer of a synthetic nutritional material (UP20) was examined at a constant H 2 S concentration (100 ppmv). The impact of the empty bed residence time (EBRT) on process performances was clearly underlined by varying the polluted air flow from 4 to 20 m 3 h −1 corresponding to a variation in the EBRT from 63 to 13 s. Complete H 2 S degradation was observed when the EBRT was higher than 51 s. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
(14 reference statements)
1
15
0
Order By: Relevance
“…Figure 5 also shows that the lower the flow rate, the higher the RE would be. This result is similar to the research of Jaber et al [8] which showed that decreasing the loading rate from 39.6 g m -3 h -1 to 9.9 g m -3 h -1 could increase RE from 45% to 100%.…”
Section: Fig 5 Performance Of Bio-filter At Various Flow Rates and Isupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 5 also shows that the lower the flow rate, the higher the RE would be. This result is similar to the research of Jaber et al [8] which showed that decreasing the loading rate from 39.6 g m -3 h -1 to 9.9 g m -3 h -1 could increase RE from 45% to 100%.…”
Section: Fig 5 Performance Of Bio-filter At Various Flow Rates and Isupporting
confidence: 82%
“…Spigno and Nicolella [7] presented the model consist of mass balance equations and accounting for reaction, mass transfer and axial dispersion to describe the steady-state degradation of phenol in a biofilter. Meanwhile Jaber et al [8] were derived the α lump parameter which enables the performance of the bio-filter as a whole to be characterized whatever its composition (mixture or layers of different packing materials) and whatever the EBRT (empty bed residence time).…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic constant was in the range between 0.0025 and 0.0092 s −1 . To our knowledge, Ottengraf's model has not be applied to biogas desulfurization, although studies on H 2 S removal from air have been modeled using Ottengraf's model [30][31][32][33].…”
Section: Ottengraf's Modelmentioning
confidence: 99%
“…Some previous researchers who have done modelling in the process of gas and liquid waste handling using biofilters include Spigno et al [18] in the elimination of phenol, Majumder et al [19] in the process of removal of divalent copper dissolved in water, Jaber et al [20] in modelling bio-filters for hydrogen sulphide contained in the air, Meena et al [21] makes the mathematical modelling of the separation of a mixture of hydrophilic (methanol) and hydrophobic (α-Pinene), Santos et al [22] used a mathematical model for the removal of hydrogen sulphide by oxidation in the bio-filter, Kim and Deshusses [23] calculate the mass transfer coefficient on the packing material used for bio-filter, either in the gas layer or the liquid layer. Furthermore Yang et al [24] makes modelling of porosity variations of bio-filter equipment used in rotary drum, Ramirez et al [25] studied the kinetics of microbial growth and biodegradation of methanol and toluene, De Visscher and Li [26] studied the disappearances modelling toluene contained in the air, Agarwal et al [27] studied the mass balance for phenol degradation events.…”
Section: Mathematical Modelsmentioning
confidence: 99%